Tudatos vásárlók a használt termékek piacán: CONSCIOUS CONSUMERS ON THE MARKET OF SECOND-HAND PRODUCTS - Kiss, Virág Ágnes; Balsa-Budai, Nikolett (Közép-Európai Közlemények, 2020)
After the latest climate conference held in Paris, the participants undertook to switch into a low carbon- dioxide-emissive economy within a frame of a concrete acting plan. In order to reach it steps were determined for the civil society as well – citizens, industry, trade unions and companies – which steps are mostly related to comsuming and lifestyle. One of its most important element is the spreading of the second-hand trading. Buying used objects maintains to decrease our ecological footstep, and help us to realise an environmentally conscious behaviour. The main reason of it is the fact that the second hand products save that pollutant-emission and material usage needed for manufacturing new products, moreover it facilitates waste management. The basis of our research was a questionnaire poll, where we would like to examine deeper those consuming groups who are already engaged to a more conscious lifestyle. We involved 301 members, and used main component- and cluster examining methods. Based on the results we can say that also in these conscious groups there are members who reject this type of recycling, together with those who are active in it, although some of them are only sellers of these types of products. To sum up, it can be assumed that based on local and international trends, the business of second hand products is a rather developing type of market, which larger and larger segments of conscious community are interested in.